Terceirização e satisfação com o trabalho - Oliveira, Ana Lúcia Amaral de (2009)
This study's mam objective is to analyze the relation between Outsourcing and Job Satisfaction. Having in mind that Outsourcing is a technique present at most organizations, it is expected to demonstrate whether it does or does not influence the employees' satisfaction on labor. The Job Satisfaction Scale - EST, in the Portuguese abbreviation -, created by Siqueira, was used in the questionnaire applied to outsourced and non-outsourced employees. That is a multidimensional scale composed by five dimensions of Job Satisfaction: in relation to co-workers, salary, leadership, nature of labor and promotions. A total of 77 answers were obtained from employees of different companies. The final result has shown that both nonoutsourced and outsourced employees are unaffected in relation to labor. The results of each dimension have shown slight differences between both type of employees. Along this study, several aspects related to outsourcing are developed, such as reasons, advantages, disadvantages and usual mistakes. Key words Outsourcing, Outsourced, Non-outsourced, Job Satisfaction